Security, AI and trust in Africa: a reflective approach - (:unkn) unknown (My University, 2024)
Artificial Intelligence (AI) can be defined as a form of computer intelligence fuelled by technological advances with the aim of improving decision-making and learning by imitating human cognitive faculties (Lollia, 2022). Today, it is invading all areas of life, in the private, professional and educational spheres, to the point of becoming indispensable or even ‘pervasive’ (Claverie et al., 2009). In Africa, where security conditions are unstable, the use of AI for ‘augmented security’ could lead to a major efficiency gain in the sector. However, it should be noted that the African continent is at an impasse on this issue. Certain reasons, such as government policy choices or a lack of confidence in security technologies, can be cited as obstacles to the development of AI in Africa. This article looks at the issue of increasing security through AI. It analyses and attempts to understand the obstacles hindering its development on the African continent and examines why its use arouses distrust.
Keywords: African Research